Effect of management system on management accounting: the case of Chinese cellular phone terminal unit manufacturers / Akira Nishimura - Nishimura, Akira (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2008)
In this paper the recent characteristics of Chinese management accounting and its genera background are examined with reference to the cellular phone terminal unit manufacturers in comparison with the Japanese situation. In particular the formation of big businesses and the effect of their management system on management accounting are clarified. At the same time, this paper refers to a bipolar divergence between the big businesses and the defeated firms in this industry which was caused by the intense price competition.